Risk factors for low bone mass in healthy young adults from North India: studies on BMD and bone turnover markers - Verma, Anita Fotedar; Verma, Ashok Kumar; Mishra, Virendra Kumar; Mandal, Sudhir Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Despite availability of adequate sunshine, Indian population has the highest prevalence of low bone mass and Bone Mineral Content (BMC). Risk factors for osteoporosis have been extensively studied in the west but poorly investigated in India. We studied BMD and Bone Turnover Markers (BTMs) among healthy young adults. Methods: Fifty one healthy young adults (28 Males, 23 Females) in the age group of 20-35 years were studied. Morphometric, biochemical parameters and BMD (whole body, spine, hip & wrist) were recorded. Anthropometric measurements included height, weight, BMI and Waist/Hip Ratio (WHR). BTMs studied included - serum Bone-Specific Alkaline Phosphatase (sBAP), serum Collagen cross-linked C-Terminal telopeptide (sCTx), serum Osteocalcin (OC) and human intact parathyroid hormone (hPTH) using standard ELISA kits. Results: Of 51 healthy volunteers 21.57% had normal BMD, 13.73% were frankly osteoporotic and 64.70% were osteopenic. Age, weight and BMI were the best predictors of total BMD and BMC at all sites. sCTX positively correlated with Total Bone Area (TBA), BMD at Hip and Forearm. Using multiple regressions - age, weight, and BMI were significant predictors of BMD in young adults. Percentage body fat had inverse correlation with BMC, BMD and TBA. Weight and height positively correlated with BMD at femoral neck, inter-trochanter and Ward’s triangle. Body weight was best predictor of BMD at femoral neck, Ward’s triangle, forearm UD, forearm MID and forearm1/3. Conclusion: Majority of healthy young Indians have poor bone health as evidenced by bone markers.